Imtaq-Based Solar System Learning in Improving Mastery of Concepts and Religious Attitude Towards Madrasah Tsanawiyah Students - Diana Widyosari; I. D. Pursitasari; D. Ardianto (JSEP (Journal of Science Education and Practice), 2021)
This experiment research aims to measure the mastery of students’ concepts and religious attitude on solar system learning based on IMTAQ. The research was conducted on class VIII MTsN 22 Jakarta in 2017/2018. The model used in this research is a Problem Base Learning with the research design of pretest posttest control group design. The use of this research design involves two classes as research samples, one experiment class and one control class. The selection of these two classes is done by taking the subject not based on strata, random or regional but based on certain goals. The research subjects were divided into two groups, namely the experiment group and the control group. The experiment grup get Problem Base Learning model based on IMTAQ, while the control grup  just get a Problem Base Learning model. The result of mastery of the concept of the experiment and control class each obtained an average gain of 49.7 and 43.7. This shows that the average pretest score of the two classes is not much different. Increasing the mastery of concepts and religious attitudes of MTsN students on the solar system material can be concluded that the average N-gain in the control class is 0.44% in the medium category, while in the experimental class the average N-gain is 0.50% in the medium category.